Structure of the Intermediate Phase Glasses GeSe3 and GeSe4: The Deployment of Neutron Diffraction With Isotope Substitution - Rowlands, Ruth F.; Zeidler, Anita; Fischer, Henry E.; Salmon, Philip S. (Frontiers in Materials, 2019)
The method of neutron diffraction with isotope substitution was used to measure the full set of partial pair-correlation functions for each of the network-forming glasses GeSe$_3$ and GeSe$_4$, which lie at the boundaries of the so-called intermediate phase in the Ge-Se system. The results show the formation of chemically ordered networks, where selenium chains are cross-linked by Ge(Se$_4$)$_{1/2}$ tetrahedra, in contrast to glassy GeSe$_2$ where the chemical order is broken. In all of these materials, the Ge-centered structural motifs are distributed unevenly on an intermediate length scale, as indicated by the appearance of a first-sharp diffraction peak in the Bhatia-Thornton concentration-concentration partial structure factor. The new experimental work provides benchmark results for guiding in the development of realistic structural models, which can be used to explore the network rigidity and other structure-related properties of the glass. In this context, there are discrepancies between experiment and the predictions of first-principles molecular dynamics simulations that are particularly marked in respect of the Ge-Ge correlation functions, which are sensitive to the connectivity of the Ge-centered structural motifs.